THE ROLES OF FINANCIAL SELF EFFICACY AND MENTAL ACCOUNTING IN INCREASING FINANCIAL MOTIVATION AND BEHAVIOR - Wirawan ED Radianto; Tommy Christian Efrata; Liliana Dewi; Laij Victor Effendi; Ika Raharja Salim (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The aim of this research is to test the influence of mental accounting and motivation to financial behavior and test financial self-efficacy in mediating the relationship between mental accounting and financial behavior. This research uses survey method by sending questionnaires to young entrepreneurs starting a business. The result of the research shows that mental accounting, financial self-efficacy, and motivation influence financial behavior. This research discovers that a person’s confidence in their ability in managing finance depend on mental accounting mindset. Financial self-efficacy is also an important variable for encouraging the increasing of a person’s ability in planning and managing finance.